IMPACT OF PM2.5 EXPOSURE ON MATERNAL AND NEONATAL HEALTH IN GLOBAL CLIMATE CHANGE - Sugiyani Sugiyani; Tustika Aristawati; Disa Larasati (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
Introduction: Climate change and air pollution, particularly PM2.5, are critical global concerns. PM2.5 refers to fine particulate matter with a diameter of less than 2.5µm, capable of penetrating the lungs and entering the bloodstream, leading to severe health issues, especially for pregnant women and neonates. This study aims to analyze the impact of PM2.5 exposure on maternal and neonatal health in the era of global climate change and to develop mitigation strategies that midwives can implement. Method: A literature review was conducted following PRISMA guidelines. The databases searched included PubMed, SagePub, and ScienceDirect, yielding 303 articles based on keywords such as risk factors, impact, negative effects, air pollution, pregnancy, maternal and neonatal outcomes, and PM2.5. After screening, 15 relevant studies were selected for review. Discussion: PM2.5 exposure has been linked to adverse pregnancy and birth outcomes worldwide, including fetal growth restriction, low birth weight (LBW), small for gestational age (SGA), preterm birth, and increased neonatal morbidity and mortality. While some studies have examined the relationship between PM2.5 and seasonal variations in pregnancy outcomes, the biological mechanisms remain unclear. Midwives can help mitigate these effects through education on air circulation, lighting, green spaces, and reducing household burning, alongside interdisciplinary collaboration. Conclusion: PM2.5 exposure during pregnancy, exacerbated by climate change, has been confirmed to contribute to poor birth outcomes. Mitigation efforts are essential to protect maternal and neonatal health.